Tornado wind hazard mapping and equivalent tornado design wind profile for Canada. (July 2021) - Hong, H.P.; Huang, Q.; Jiang, W.J.; Tang, Q.; Jarrett, P.
Highlights: Developed model for tornado occurrence rate for Canada based on the generalized linear model. Identified preferred stochastic tornado occurrence model based on the database and covariates. Developed the Canadian tornado hazard map in terms of the wind speed at 10 m height above the ground. Proposed a simple equivalent tornado design wind profile which is the first of its kind. Abstract: Tornadoes cause property damage and fatalities. A systematic assessment of tornado wind velocity hazard is presented in the present study for Canada based on reported historical tornado catalogue. For the assessment, the Poisson model, zero-inflated Poisson model, and negative binomial model, as well as the adaptive Gaussian kernel smoothing technique, are used to model tornado occurrence. The modeling takes into account the tornado reporting bias due to population density and uses the cloud-to-ground lightning flash density and the thunderstorm days as the explanatory variables. Statistical analysis results indicate that the negative binomial model is preferable. The tornado wind velocity hazard maps for Canada, in terms of wind velocity at 10 m height above the ground surface and return period T, VT (10), are developed based on an available probabilistic tornado wind field model. Also, a simple equivalent tornado design wind profile is developed based on the return period value of tornado wind speed at different heights. The developed tornado design wind profile only depends on VT (10), which greatly facilitates its potential use for structural design subjected to tornado wind load and its possible implementation in structural design code and standards.